2009
DOI: 10.1037/a0015912
|View full text |Cite
|
Sign up to set email alerts
|

Asian international doctoral students’ experiences at two American universities: Assimilation, accommodation, and resistance.

Abstract: The purpose of this study was to explore and describe the sojourn experiences of Asian international students enrolled in graduate programs at American universities. The six participants (3 women, 3 men) were Japanese, Korean, and Taiwanese doctoral students at two universities in the Big Ten Conference. The research design was exploratory multiple-case study (R. K. Yin, 2003) informed by the concept of the Sojourner (P. C. P. Siu, 1952) in terms of assimilation, accommodation, and resistance. The primary data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
74
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 108 publications
(85 citation statements)
references
References 17 publications
9
74
1
1
Order By: Relevance
“…This means that students perceived faculty as more than just their advisors. This finding is inconsistent with another study (Sato & Hodge, 2009). They reported that Asian international student's relationship with faculty tended to be more academic than social relationships.…”
Section: Utility For Careercontrasting
confidence: 57%
See 4 more Smart Citations
“…This means that students perceived faculty as more than just their advisors. This finding is inconsistent with another study (Sato & Hodge, 2009). They reported that Asian international student's relationship with faculty tended to be more academic than social relationships.…”
Section: Utility For Careercontrasting
confidence: 57%
“…The result of faculty influence matched with the line of study that the relationship with Asian international doctoral students and their advisors helped most likely to succeed in their graduate programs (Sato & Hodge, 2009). Since it is not easy for Asian international students to navigate graduate programs smoothly due to aforementioned issues in the introduction, the influence of faculty is inevitable.…”
Section: Faculty Influencementioning
confidence: 89%
See 3 more Smart Citations